2020
DOI: 10.6007/ijarbss/v10-i4/7112
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Employee Absenteeism in Oil Palm Estate

Abstract: Employee absenteeism is one of the problems in oil palm plantation. This behavior leads to low productivity and high burdening business cost. This study aims to examine, analyze and explain the influence of stress, family issues, working environment and salary to employee absenteeism in oil palm estate. The primary data used in this study come from questionnaire on respondents' stress, family issues, working environment, salary and employee absenteeism. From 90 people as the population, 73 respondents who met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Workers must work in favorable conditions such as health and wellbeing, and safety. The statement is supported by other researchers that also reported the same concept of employees' motivation or morale that can be influenced by the unavailability of excellent working conditions which can discourage them from reporting to their workplace [2].…”
Section: Correlation Analysismentioning
confidence: 52%
See 2 more Smart Citations
“…Workers must work in favorable conditions such as health and wellbeing, and safety. The statement is supported by other researchers that also reported the same concept of employees' motivation or morale that can be influenced by the unavailability of excellent working conditions which can discourage them from reporting to their workplace [2].…”
Section: Correlation Analysismentioning
confidence: 52%
“…Commonly, the remuneration factor depends on the employer since they are the ones who will offer the remuneration such as salary, bonuses, or allowances to their workers. The result of the study shows that among all the other factors that contribute to absenteeism among oil palm workers, wages have the least significance to the problem [2]. Hence, we can say that remuneration that includes salary, bonuses, reward, and allowances does not affect many workers since most plantation companies provided house allowance, health insurance and other allowances to their employees.…”
Section: Correlation Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies showed that workers' behaviour is crucial in determining the performance of an organization (Wright et al, 2005;Ibitoye et al, 2011;Raza et al, 2014;Nawi et al, 2016;Johari & Jha, 2020;Truong & Le, 2020). Specifically, the studies by Zulkefli et al (2018); Syahlan et al (2020) discovered the influence of workers' behaviour in oil palm plantations on plantation productivity and business cost. To achieve an increase in output, plantations need to have a consistently skilled workforce (Ahmad et al, 2017).…”
Section: Introductionmentioning
confidence: 99%